2008
DOI: 10.1074/jbc.m802655200
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the Chromodomain Y Chromosome Family of Chromodomains for Lysine-methylated ARK(S/T) Motifs

Abstract: Previous studies have shown two homologous chromodomain modules in the HP1 and Polycomb proteins exhibit discriminatory binding to related methyllysine residues (embedded in ARKS motifs) of the histone H3 tail. Methylated ARK(S/T) motifs have recently been identified in other chromatin factors (e.g. linker histone H1.4 and lysine methyltransferase G9a). These are thought to function as peripheral docking sites for the HP1 chromodomain. In vertebrates, HP1-like chromodomains are also present in the chromodomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 47 publications
5
90
2
1
Order By: Relevance
“…Previous studies have shown that Cdyl can interact with various histone marks, including H3K9me2, H3K9me3, and H3K27me3 (20,21,54). Cdyl has also been reported to interact with the G9a protein, as confirmed here.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have shown that Cdyl can interact with various histone marks, including H3K9me2, H3K9me3, and H3K27me3 (20,21,54). Cdyl has also been reported to interact with the G9a protein, as confirmed here.…”
Section: Discussionsupporting
confidence: 69%
“…The chromodomains of polycomb and HP1 were shown to specifically recognize conserved ARK(S/T) motifs in the tail of histone H3 (supplemental Fig. S5A) (31)(32)(33). A closer inspection of motifs II and IV in A3CT showed that they contain AKRS and SKRS sequences reminiscent of ARK(S/T) motifs in the histone H3 tail ( Fig.…”
Section: The Alb3-cpsrp43 Interaction Requires Two Positively Chargedmentioning
confidence: 99%
“…Transcritional silencing, heterochromatin SUV39H1/2 [143] , G9a [248] , SETDB1 [249] JMJD1A/KDM3A [250] , JMJD1B/KDM3B [251] , JMJD1C/TRIP8, JMJD2A/KDM4A (B/C/D) [252] HP1 [253] , EED 17406994), TDRD7 [254] , MPP8 [255] , UHRF1/2 [256] , GLP [248] , CDY FAMILY [257] H3K27 me1/me2/me3, heterochromatin and facultative heterochromatin Transcritional silencing, heterochromatin, poised genes EZH2, EZH1 [258] JMJD1A/KDM3A, JMJD1B/KDM3B, KDM6A/UTX, JMJD3/KDM68, JMJD3/KDM6B [259] Cbx proteins [165] , EED [260] [ 166,261] H3K36 Ac Transcription activation GCN5, PCAF [244] [262]…”
Section: H3k27me3 or H3k9me3mentioning
confidence: 99%